2016
DOI: 10.1186/s13104-016-2000-z
|View full text |Cite
|
Sign up to set email alerts
|

HPLC profiling, antioxidant and in vivo anti-inflammatory activity of the ethanol extract of Syzygium jambos available in Bangladesh

Abstract: BackgroundSyzygium jambos has been used as a traditional medicine for the treatment of inflammatory diseases in Bangladesh. The study investigates the high performance liquid chromatography (HPLC) profiling of phenolic compounds, and evaluates the antioxidant and anti-inflammatory activities of ethanol extract of S. jambos available in Bangladesh.MethodsThe extract was subjected to HPLC for the identification and quantification of the major bioactive polyphenols present in S. jambos. Antioxidant activity was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…For ABTS •+ assay, the standards showed a stronger antioxidant activity when compared to PESc. Despite this, as far as we know, PESc showed the lowest IC 50 against ABTS •+ for a S. cumini extract described thus far [ 39 , 40 ]. ABTS •+ is reactive through both hydrophilic and hydrophobic radicals while DPPH • assay is performed in organic solvents where hydrophobic radicals reduce the radical [ 41 ].…”
Section: Discussionmentioning
confidence: 80%
“…For ABTS •+ assay, the standards showed a stronger antioxidant activity when compared to PESc. Despite this, as far as we know, PESc showed the lowest IC 50 against ABTS •+ for a S. cumini extract described thus far [ 39 , 40 ]. ABTS •+ is reactive through both hydrophilic and hydrophobic radicals while DPPH • assay is performed in organic solvents where hydrophobic radicals reduce the radical [ 41 ].…”
Section: Discussionmentioning
confidence: 80%
“…When compared with the control tube, the tubes in which the extract was exposed to light in contact conditions and absence with oxygen, we observed that the extract components are photosensitive, as well as sensitive to oxygen content. These results may explain the antioxidant effect of the extract reported by [13].…”
Section: Discussionsupporting
confidence: 60%
“…The phenolic composition of the ethanol extract of T. dioica peel extract was determined by Dionex UltiMate 3000 HPLC system (Thermo Scientific, equipped with PDA (DAD-3000RS)), as described previously [15,16].…”
Section: Hplc-dad Analysismentioning
confidence: 99%